DEVELOPMENT OF INNOVATIVE APPROACHES IN ECONOMICS STUDENTS - Abdiyeva Dilfuza Kurbanovna (Ecominds Press, 2025)
This article sets out the main tasks of preparing students studying in higher education institutions as competitive economists, with the aim of training specialists who, along with deep theoretical and practical knowledge, can work independently in their chosen field, independently improve their knowledge and skills, correctly identify and analyze problematic situations with a creative approach to the issue, and quickly adapt to the conditions.
Keywords: Education, independent activity, Student, Task, preparation, necessity, problem, thinking, interest.